Sugar guess who's coming for dinner in the new millenium? - Barret, Neil; Video Education Australasia (Australia : Video Education Australasia, 2000)
The more sugar we eat, the less complex carbohydrate and the more fat we eat. For that reason, sugar, with its empty kilojoules, is a food we should eat less
Title from tite screen
Executive producer, Stephen Skok ; editor, Sasha Trikojus ; sound, Joel de Courcy Browne ; camera, Walter Repich
Narration: Jenny Tudor
Keywords: Sugar